Dynamically Controlled Electronic Behavior of Stimuli‐Responsive Materials: Exploring Dimensionality and Connectivity. Issue 4 (30th April 2021) - Leith, Gabrielle A.; Martin, Corey R.; Mathur, Abhijai; Kittikhunnatham, Preecha; Park, Kyoung Chul; Shustova, Natalia B.
Abstract: Materials with dynamically controlled electronic structures (i.e., upon external stimuli) are at the forefront of the renewable energy sector with applications as memory devices, smart supercapacitors, programmable solar cells, and field‐effect transistors. Moreover, their continued development as device components is critical for the field of optoelectronics since their performance is comparable, or could even surpass, the current benchmarks. Adaptive electronic properties are the main focus of this review that discusses recent developments in the modulation of electronic behavior that can be tuned using external stimuli in metal–organic frameworks (MOFs), covalent–organic frameworks (COFs), primarily inorganic hybrids, polymers, and graphitic‐type materials. Triggers to achieve "dynamic" behavior discussed within this manuscript are primarily light‐based switches that include different classes of photochromic molecules such as naphthalene diimide, viologen, diarylethene, azobenzene, and spiropyran. The effect of material dimensionality and photoswitch connectivity achieved through integration of photochromic moieties inside 0D, 1D, 2D, and 3D hybrid matrices is discussed. This review showcases the prospects of advancing the material and energy landscapes through employment of structural motifs with adaptive electronic structures occurring as a function of their dimensionality and connectivity. Abstract : The desire to explore the convergence of electronic properties, dimensionality of materials, and connections of photoswitchable molecules has led to momentous progress in the field of stimuli‐responsive materials. Their applications as memory devices, smart supercapacitors, programmable solar cells, and field‐effect transistors can bring dynamically controlled photoresponsive motifs to the forefront of material engineering.